2014
DOI: 10.1136/neurintsurg-2014-011437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of carotid artery stenting for asymptomatic and symptomatic carotid artery stenosis: a single-center prospective study

Abstract: Periprocedural and long-term follow-up outcomes of CAS appear similar for ACS and SCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Sakai et al 10 found that the risk of any stroke was 5.7% within 30 days after CAS, whereas it was only 1.6% from 31 days to 1 year. Mo et al 11 also published the rates of composite vascular event (stroke, AMI, and death) after CAS which were 1.5% within 30 days and 4.5% under mean 18.3 months of follow-up. Long-term outcomes after international carotid stenting study (ICSS trial) demonstrated that cumulative 1-year stroke rate was 9.5%; however, if it only included patients >30 days post-CAS, the rate was found to be 2.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Sakai et al 10 found that the risk of any stroke was 5.7% within 30 days after CAS, whereas it was only 1.6% from 31 days to 1 year. Mo et al 11 also published the rates of composite vascular event (stroke, AMI, and death) after CAS which were 1.5% within 30 days and 4.5% under mean 18.3 months of follow-up. Long-term outcomes after international carotid stenting study (ICSS trial) demonstrated that cumulative 1-year stroke rate was 9.5%; however, if it only included patients >30 days post-CAS, the rate was found to be 2.9%.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Moreover, the follow-up time in most of the published studies in China is less than 2 years, and few data has identified the safety of CAS among the older patients. [12][13][14] Therefore, we aimed to compare the demographic and clinical characteristics, and periprocedural and an extending 5-year event rates between younger (<70 years) and older (≥70 years) patients treated by CAS at a single institution to testify the safety of CAS in older patients in China.…”
Section: Introductionmentioning
confidence: 99%
“…Karotid arter stenozu genel olarak geriatrik hasta grubunda görülen bir hastalıktır [1,2]. Karotid stenozu tedavisinde gerek endarterektomi ve stentleme etkin bir yöntem olup karşılaştırmalı pek çok çalışma mevcuttur [3,4]. Karotid stenozu tedavisinde stent ile tedavinin getirdiği morbidite ve mortalite riskinde yaşa bağlı bir artış olup olmadığı hakkında randomize ve çift kör çalışmalar oldukça kısıtlıdır.…”
Section: Introductionunclassified